Analysis of risk management of online queue innovation system services (SINOVA) Bantul Regency - Saputra, Yoga Aldi; Aknesia, Vharessa; Fitri, Zaneta Cahaya; Achmad, Dewi Hardiana (Universitas Merdeka Malang, 2023)
Public governance is a concept that describes the government's ability to fulfill people's satisfaction and achieve people's prosperity. Currently, the government is required to improve risk management to deal with various challenges that come quickly, uncertainly, and minimize the possibility that they will occur in the future. One form of risk management is through Governance, Risk, and Control (GRC). The Disdukcapil of Bantul Regency issued a website-based service that is expected to be able to provide convenience for the people of Bantul who experience problems in processing population documents. This article aims to understand and describe the application of risk management principles carried out by the Disdukcapil of Bantul Regency during the COVID-19 pandemic using a qualitative approach using the case study method. The results showed that risk management carried out through website-based services had not been fully responded to by the community, so Disdukcapil delegated tasks by opening Adminduk services in sub-districts. This is in response to reducing queue buildup during the Covid-19 pandemic.